Somniloquy: Augmenting Network Interfaces to Reduce PC Energy Usage - Agarwal, Yuvraj; Hodges, Steve; Chandra, Ranveer; Scott, James; Bahl, Victor; Gupta, Rajesh (Networked Systems Design & Implementation (NSDI), 2009)
Reducing the energy consumption of PCs is becoming increasingly important with rising energy costs and environmental concerns. Sleep states such as S3 (suspend to RAM) save energy, but are often not appropriate because ongoing networking tasks, such as accepting remote desktop logins or performing background file transfers, must be supported. In this paper we present Somniloquy, an architecture that augments network interfaces to allow PCs in S3 to be responsive to network traffic. We show that many applications, such as remote desktop and VoIP, can be supported without application-specific code in the augmented network interface by using application-level wakeup triggers. A further class of applications, such as instant messaging and peer-to-peer file sharing, can be supported with modest processing and memory resources in the network interface. Experiments using our prototype Somniloquy implementation, a USB-based network interface, demonstrates energy savings of 60% to 80% in most commonly occuring scenarios. This translates to significant cost savings for PC users.